Investigating the cross-species invasion events of monkey malaria parasites into human red blood cells - Devakumar, Aishwarya (Nanyang Technological University, 2022)
Plasmodium knowlesi (P. knowlesi), a zoonotic malaria parasite, causes potentially severe symptoms and has shown an increasing incidence of cross-species transmissions in Southeast Asia. Despite the growing concerns of P. knowlesi infections in human red blood cells (RBCs), its invasion events and host-parasites interactions are still unclear. Thus, previous methods used to study P. falciparum invasion were implemented to investigate P. knowlesi blood-stage invasion event. Interestingly, in the presence of cyclic adenosine monophosphate (cAMP) signalling inhibitors, fluorescence plate reader and live microscopy, P. knowlesi demonstrated to activate the same Ca2+ signalling pathway in RBC as P. falciparum via cAMP signalling. G-protein and cAMP-dependent protein kinase catalytic subunit alpha (PKA) are essential members of the pathway. In P. falciparum, the species-specific protein reticulocyte-binding homolog 5 (RH5) binds to basigin to trigger RBC Ca2+ influx but attempts to identify an RH5-like protein were unsuccessful in P. knowlesi. Nevertheless, this study proves the invasion event into human RBC is conserved between species and the ligand that triggers RBC Ca2+ flux in P. knowlesi invasion is likely a membrane protein. Hence, this knowledge can facilitate the development of interventions and reveals information regarding an essential host cell signalling conservation during invasion of Plasmodium parasites.